Biochemical Defense Induction In Indian Mustard (Brassica Juncea L.) And Rapeseed (B. Napus L.) By Salicylic Acid And Benzothiadiazole (Applied Biological Research, 2014)
Alternaria blight, caused by Alternaria brassicae (Berk.) Sacc., is one of the  serious diseases of Brassica species. A field experiment was conducted to  evaluate the effects of two elicitors, salicylic acid (SA) and benzothiadiazole  (BTH), on defense response induction in Brassica juncea and B. napus against Alternaria blight. Four different treatments of SA and BTH were  given to 10 week old plants upto 4 consecutive weeks. Chitinase and β-1,3- glucanase enzyme activities; and ascorbic acid and pigment contents were  assessed 72 hr after treatment and disease incidence recorded a week after  spray. Hydrolytic enzymes activities attained maximum level after 2nd spray  in treatment combinations BTH (3 ppm) + SA (33 ppm) and BTH (7 ppm) +  SA (17 ppm). An increase in ascorbic acid and pigment contents was  observed in all the treatments after 1st, 2nd and 3rd spray followed by a  decrease after 4th spray. Maximum increase was seen in treatment  combinations of elicitors. These treatments also reduced Alternaria blight  severity in both the species. The elicitors, applied in combinations, showed  synergistic effect on the induction of hydrolytic enzyme activities as well as ascorbic acid and pigment contents in comparison to the individual  applications. The study showed that the elicitor combinations can be used  effectively to combat Alternaria blight in Brassica species.
Keywords: Ascorbic acid; β-1; 3-glucanase; benzothiadiazole; Brassica; chitinase; chlorophyll; salicylic acid